1001 Nights and Anime: The Adaptation of Transnational Folklore in Tezuka Osamu's Senya ichiya monogatari/A Thousand and One Nights (1969). Issue 1 (1st June 2021) - Denison, Rayna; Van de Peer, Stefanie
Abstract : Anthologising folktales from across the Middle East and North Africa, the inherently transnational 1001 Nights has become one of the most adapted works in the history of folklore (Zipes et al. 2015). The tales have been adapted globally into works ranging from literature to theatre, from radio to film and animation. The animated versions of the tales in particular, refer to some of the earliest feature films in animation history and have been the subject of debate concerning their representational strategies (Sterritt 2020 ; Belamghari 2015 ). The treatment of the tales by Japanese media producers affords us a way to decentre the significance of these earlier and more lauded Euro-American adaptations and to consider how these transnational tales flowed to, and were appropriated and reinterpreted within, other parts of the world. First translated into Japanese in 1875, the 1001 Nights quickly went on to gain a foothold within Japanese literature, and more recently it has become the basis for numerous manga and anime adaptations (Nishio and Yamanaka, 2006 ). This article investigates how one animated Japanese adaptation by famed manga artist Osamu Tezuka, Senya Ichiya Monogatari (dir. Eiichi Yamamoto, 1969 ), expands the transnational status of the original through its appropriation into anime's aesthetic and cultural repertoires. In exploring how the 1001 Nights have become and remain integral to a transnational repertoire of animated storytelling, we examine the elasticity and transnationality of 1001 Nights and the implications of its cultural localisation in Japan. We argue that the original's structural and thematic emphasis on journeys, quests and flows provides the Japanese filmmakers with subject matter designed to flow, making the tales an attractive adaptation source for Japanese filmmakers who were themselves seeking greater transnational reach for their animated films. Within this set of flows, a reciprocal transnationality can be found in the 1001 Nights and its adaptation into anime, offering a mechanism for rethinking the relationships among Middle-Eastern, North African and Japanese forms of storytelling.